A Preliminary Study on Microbial Contamination of Leafy Vegetables in Sokoto Metropolis, Nigeria - Kasimu Shehu; Asma’u M. Maishanu; Ibrahim A. Salau (Graduate Program of Syiah Kuala University, 2014)
Five leafy vegetables commonly consumed in Sokoto metropolis were evaluated for microbiological quality using standard procedures involving standard plate count (SPC). The vegetables investigated included Lactuaca sativa (Lettuce), Amaranthus hybridus (Spinach), Vernonia amagdalina (Bitter leaf), Brassica oleracea (Cabbage) and Moringa oleifera Lam (Horse radish). Ten fungal species which include Alternaria alternata, Absidia corymbifera, Aspergillus niger, A. flavus, Cladosporium herbarum, Fusarium oxysporium, Geotrichum candidum, Mucor racemoses, Rhizopus stolonifer and Trichoderma harzianum and four species of bacteria: Bacillus cereus, Escherichia coli, Listeria monocystogens and Staphyllococus aureus were isolated from the leafy vegetables. The total colony counts of fungi ranged from 1.8 x 106 – 6.28 x 105 (cfu/g) of the vegetables while that of bacteria ranged from 1.0 x 106 to 2.94 x 106 cfu/g of the vegetables. The highest counts of microbial organisms were found on A. hybridus while M. oleifera and B. olerarea had the lowest fungal and bacterial counts respectively. There is a need to reduce the levels of microbial contamination on leafy vegetables through appropriate production practices, careful handling by the vendors and appropriate processing with a view to minimize the risk of human exposure to fungal and bacterial pathogens associated with the vegetables.